Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat dan Implikasinya Terhadap Pembangunan Ekonomi - Hasibuan, Fadli Hasbi; Siagian, Kurnia Fitri; Zein, Ahmad Wahyudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of public service quality on community satisfaction and its implications for economic development. High-quality public services are believed to enhance public trust and satisfaction, which in turn contribute to creating a more favorable environment for economic development. The research employs a quantitative approach, with data collected through questionnaires distributed to the public as respondents. The analysis reveals a positive and significant relationship between public service quality and community satisfaction, with the latter acting as a mediating variable that strengthens the impact on economic development. These findings highlight the importance of improving public service quality as a strategic effort to accelerate inclusive and sustainable economic development.